Analisis Fiqih Komperatif Atas Larangan Pernikahan Sedarah dalam Pustaka Hukum Islam - Anisatul Haniah; Naili Nadhifah; Dewi Khoirun Nisa; Kustini, Yurid Ilyuna; Mohammad Syaifuddin (Konsorsium Dosen Sekolah Tinggi Agama Islam (STAI) Al-Yasini Pasuruan, 2025)
Marriage between close relatives, such as twins or siblings, is an important topic in Islamic law, encompassing legal, social, and ethical aspects. The four main schools of Islamic jurisprudence (fiqh), namely Hanafi, Maliki, Shafi'i, and Hanbali, have different views on the degree and scope of such marriages' prohibition. Their views are based on scriptural texts and considerations of maslahah (public interest). Findings from modern medicine also support the social and biological reasons for prohibiting marriage between close relatives, such as the increased risk of genetic diseases and birth defects in children. Although most scholars agree on the strict prohibition of consanguineous marriage, there are still differences in the interpretation of certain boundaries, especially in cases of unclear kinship or issues of legal branches. To address the challenges of family law today, a contextual and comparative approach to fiqh between schools is crucial. This approach also helps integrate scientific findings without the limitations of textual authority. Therefore, building a legal system that is just, accommodating, and remains based on Islamic law remains an important task to safeguard the welfare of the people and ensure that Islamic law can develop in accordance with the present.